Determination of Hotel Room Rental Rates during Low Season with the Break-Even Point Analysis Method at Aston Hotels International - Rachmad Chartady; Salihi Salihi; Andres Putranta Sitepu; Bambang Sambodo (Budapest International Research and Critics University, 2021)
This study aims to determine how much room rental rates at Aston Hotel Tanjungpinang during the low season in 2020 using the break-even point analysis method so that the company can increase the room occupancy rate during the low season and not experience business losses, the researcher determines the research subject where the selected resource persons are. have competence and in accordance with data needs, while the sampling technique used is purposive sampling. This research is a qualitative research, the types of data used in this study are secondary data and primary data, while the data collection techniques are obtained through observation, interviews and literature study.Break even point is a condition which indicates that the amount of revenue received by the company (total revenue) is equal to the amount of costs incurred by the company. To achieve a break-even point analysis, the minimum occupancy should reach 81.93% per month, the results calculation of the break-even point analysis or break event point rental rates for room rates with studio type of IDR 403,966, - then for the superior room type of IDR 449,179, -, deluxe room type of IDR 463,694-, the premier deluxe room type is IDR 566,727, - while the junior suite is IDR 566,727, - and the president suite of IDR 750,087, -